ANALISA SISTEM PEMBANGKIT THERMOELEKTRIK DENGAN RANGKAIAN PARAREL PADA PEMANFAATAN PANAS BUANG MESIN TOYOTA COROLLA EFI - Wibowo, Agus; ., Zulfah; Anggianto, Prawiro (Universitas Pancasakti Tegal, 2011)
In the coming year is estimated to be growing energy needs increased by about 40% ofcurrent needs, as we know from 100% fuel used by only about 30% that is used to drive thecar. part of the energy wasted in the form of the radiator and the gas is wasted purpose ofThis analysis is to determine how to utilize waste heat energy in toyota corolla engineefficiently into energy useful to the system and to determine the effect thermolektrik parallel circuit thermoelektrik components generated strong currents and voltages generatedelectricity in accordance with the type of materials used.In writing this essay the author collected data - data with methods of literature, interviews and observation.There results can be conclude (1) for exhausted heat energy in Corrola EFI Toyota engines are asw follows. Arranging thermoelektrik with parallel circuit which is mounted on the exhaust side, turn the machine with 1000 rpm engine speed, gradually up to 300 0 rpm. Start measuring the temperature of top and bottom of these thermoelektrik, and also a strong measure of current, voltage to be produced thermoelektrik. There we received the results from the engine exhaust heat is on with a series of parallel thermoelektrik. (2) there researchon the influence of these parallel series of studies thermoelektrik components that wereassembled in parallel to produce strong currents and tension resulting from the wasteexhaust heat is wasted. at 1000 rpm to produce strong currents of 0.5 degrees Celsiusampere and voltage of 0.9 volt temperature - average above 45 degrees Celsius, the temperature - average 95 degrees Celsius below 1500 rpm to produce strong currents of 0.9ampere and voltage of 1 volt and temperature - average 59 degrees Celsius.temperature - average below 111 degrees Celsius. 2000 rpm producing a strong current of 1ampere and voltage of 1.2 volts and temperatures average 61 degrees Celsius, the temperature - average below 119 degrees Celsius, 2500 rpm producing a strong current of1.5 amperes and the voltage at 1, 5 volts and temperature - average 56 degrees Celsius, the temperature ? average below 123 degree Celsius. 3000 rpm to produce strong currents of 1.5amperes and the voltage of 2 volts and temperature - average 61 degrees Celsius, the temperature - average below 127 degrees Celsius. if understood parallel pengaruhrangkaianis still very small to generate strong currents and voltages. the stronger the currents used, the greater the stronger the smaller the current and voltage and vice versa.Key words : ampere, temperature, voltase, thermoelektrik